Divide x^2-4x+1 by 2x^4-9x^3+5x^2+3x-1
wajeed810:
Someone answer fast
Answers
Answered by
1
Answer:
x^2-4x+1 by 2x^4-9x^3+5x^2+3x-1 = -8
Calculator results:
2 × 4 + 4 × 3 − 5 × 2 + 3 × -2 × 2 + 2 × -3 = -8
Answered by
5
Given f(x) = 2x⁴ - 9x³ + 5x² + 3x - 1.
Given g(x) = x² - 4x + 1
Long Division Method:
x² - 4x + 1) 2x⁴- 9x³ + 5x² + 3x - 1 (2x² - x - 1
2x⁴ - 8x³ + 2x²
---------------------------------
-x³ + 3x² + 3x - 1
-x³ + 4x² - x
---------------------------------
-x² + 4x - 1
-x² + 4x - 1
----------------------------------
0.
Therefore, Quotient = 2x² - x - 1, Remainder = 0.
Hope it helps!
Similar questions